2018
DOI: 10.1111/jfpe.12939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave and infrared drying over polyphenol content in Vaccinium meridionale (Swartz) dry leaves

Abstract: In the present work the drying of blueberry (mortiño) leaves (Vaccinium meridionale‐Swartz) was done using a hybrid equipment with infrared drying and normal microwave drying. During the drying tests there was a record of moisture content versus time; samples of leaves were taken during the drying time to analyze total phenol (PT) content, FRAP assay and catechin measures by HPLC‐DAD. The PT analysis shows that its content in dry blueberries, increased 12 times more with the microwave drying than infrarred dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…Fenugreek leaves are usually dried for further use by various methods i.e. sun drying (Shrivastava & Kumar, 2016), Solar drying (Navale et al, 2014;Shrivastava & Kumar, 2016;Singh et al, 2004), hot air drying (Bishnoi et al, 2016;Kalaskar et al, 2012), freeze drying (Kushwaha & Mustafa, 2012), convective drying (Jawake et al, 2017), fluidized bed drying (Jawake et al, 2018) and microwave based drying (Borda-Yepes et al, 2019;Hihat et al, 2017;Khan et al, 2016;Martins et al, 2019;Monton et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Fenugreek leaves are usually dried for further use by various methods i.e. sun drying (Shrivastava & Kumar, 2016), Solar drying (Navale et al, 2014;Shrivastava & Kumar, 2016;Singh et al, 2004), hot air drying (Bishnoi et al, 2016;Kalaskar et al, 2012), freeze drying (Kushwaha & Mustafa, 2012), convective drying (Jawake et al, 2017), fluidized bed drying (Jawake et al, 2018) and microwave based drying (Borda-Yepes et al, 2019;Hihat et al, 2017;Khan et al, 2016;Martins et al, 2019;Monton et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Drying is the most common processing technique for materials preservation by preventing the microbiological spoilage (Borda‐Yepes et al, ). Microwave drying is applied as an efficient method for agricultural products dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…This is why if the research was based on the search for infrared drying information, the most keywords found were related to these topics. Some of the authors who mention the most repeated keywords in the articles are Rashid et al (2019), Daniel and Onwude (2019), Khampakool et al (2019), and Borda-Yepes et al (2019, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al (2019) used linear and algorithmic models to determine the shrinkage or reduction of the area of potato slices, managing to optimize the adjustment of the power of the microwave with which the infrared used for drying is applied. Borda-Yepes et al (2019) used the drying curves to determine the moisture present in a product, which was dried by infrared and by microwaves, concluding that microwave drying preserves better qualities than infrared does. Wang (2019) compared HAD, infrared drying, and microwave drying and determined which of these was more appropriate and presented better conditions for processing shiitake mushrooms, determining that microwave drying considerably reduced drying time and higher polysaccharide content compared to the other methods.…”
Section: Products or Found In The Readingmentioning
confidence: 99%